Mechanical properties and microstructural analysis of MICP-reinforced coarse-grained saline soils under freeze-thaw cycling - Liang Xiong; Lieyu Tian; Xiaolian Zhang; Mingxin Wang; Ailiyaer Ahemaiti (PLoS ONE, 2025)
Coarse-grained saline soils in cold regions, characterized by poor stability and low bearing capacity, pose serious risks to road and bridge infrastructure. Microbially Induced Calcium Carbonate Precipitation (MICP) is a sustainable geotechnical technique with potential for saline soil improvement, but its efficacy is compromised by high salinity and freeze-thaw cycling. In this study, sulfate coarse-grained saline soils with varying salt contents were reinforced via MICP and subjected to multiple freeze-thaw conditioning regimes. Mechanical properties and microstructural changes of the saline soils were characterized to elucidate the degradation of MICP-treated saline soils under coupled salinity and freeze-thaw effects. Results indicate that increasing salinity exerts both inhibitory and competitive effects on MICP, reducing calcium carbonate production by 80.97%. Increased numbers of freeze-thaw cycles exacerbated damage to the cementation network. Saline soils with Na 2 SO 4 ≥ 6% exhibited markedly reduced resistance to degradation: porosity-reduction magnitude fell to 12.27% and cohesion decreased to 0.057 MPa. Furthermore, the coupled effects of salinity and freeze-thaw accelerated the loss of MICP’s ameliorative efficacy in saline soil.